Universal preschool programs and long-term child outcomes: A systematic review - Jens Dietrichson; Ida Lykke Kristiansen; Bjørn C. V. Nielsen (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
What are the long-term effects of universal preschool programs on child outcomes? We review 26 studies using natural experiments to estimate the effects of universal preschool programs for children aged 0-6 years on child outcomes measured from third grade to adulthood. Studies comparing preschool with parental, family, or other informal modes of care show mixed effects on test scores, and on measures related to health, well-being, and behavior. However, all estimates for outcomes related to adequate primary and secondary school progression, years of schooling, highest degree completed, employment, and earnings indicate beneficial average effects of universal preschool programs. Three of the included studies calculate benefits-to-costs ratios and find ratios clearly above one. Universal preschool tends to be more beneficial for children with low socioeconomic status, and there are not consistently different effects for boys or girls. Only three studies compare two alternative types of universal preschool programs in terms of long-term outcomes.
Keywords: I00; I20; I24; I38; J24; Z18; 330; universal preschool; long-term effects; child outcomes; systematic review